PANDUAN LOKASI DAN AKOMODASI WISATA BERBASIS ANDROID DI YOGYAKARTA - Nurul Mega Saraswati; Budi Suhendro (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Application guides tourist sites in Yogyakarta, is a system that provides convenience to the traveler's reference to tourist sites and public facilities such as gas stations, hotels, restaurants and souvenier shops on the application. With this application accessing information to become more effective and efficient use of smartphones to better facilitate the search of tourist sites that use LBS, featuring the categories of travel (natural tourism, education and cultural / historical), provide search facility tourist sites based on cost-owned using minimal android app 2.2 (Froyo). The method of using the system development model of HIPO and relation table, the implementation phase of software development using Windows7, Javascript and MySQL database. Android based applications can facilitate the user to travel to locations with existing costs